The effect of eight weeks of walking exercise and folate supplementation on plasma homocysteine levels in elderly non-athletes - Latif Saifalddin, Dara; Qadir Hamasalah, Balen; Wahbi Ghafoor, Danar; Ahmed Rahim, Hiwa; Sirwan Mohammed, Saiwan (Jurnal Ilmu Olahraga dan Kepelatihan Indonesia, 2023)
aims / objectives of the research: The increase in cardiovascular diseases among the elderly is one of the world's leading causes of death, and aerobic exercise is one way to prevent these conditions. Aim and Objective: This study aimed to determine the effect of 8 weeks of walking and folate consumption on plasma homocysteine levels in non-athletic older women. Materials and Methods: In this experimental study, 20 non-athletic older women aged 50 to 60 volunteered to participate and were randomly assigned to one of two groups: exercise+folic acid (10 persons) or exercise+placebo (10 persons). Both groups completed a walking program of eight weeks (3 sessions per week, each lasting 60 minutes). Following the conclusion of the exercise program, blood samples were collected and analyzed using independent and dependent t-statistics. After completing the walking exercise program for eight weeks, the plasma homocysteine levels fell considerably in both the exercise+supplement (P=0.002) and exercise+placebo (P=0.005) groups. Results: After completing the walking exercise program for eight weeks, the plasma homocysteine levels fell considerably in both the exercise+supplement (P=0.002) and exercise+placebo (P=0.005) groups.Conclusion: According to the present study's findings, elderly individuals should engage in walking exercises and take supplemental folate to lower plasma homocysteine and prevent cardiovascular risks.